ESG Disclosure in Explaining Financial Performance with Firm Size as a Moderating Variable Empirical Study on Banking Sub-Sector Listed on the Indonesia Stock Exchange, 2020–2024 - Hanny Ulfa Hidayati; Nanu Hasanuh (Darul Yasin Al Sys, 2026)
Although ESG disclosure has received increasing scholarly attention, research examining the disaggregated effects of Environmental, Social, and Governance disclosure on banking profitability and the moderating role of firm size in the Indonesian banking sector remains limited. This study aimed to analyze and empirically test the effects of Environmental, Social, and Governance disclosure on the financial performance of banking companies listed on the Indonesia Stock Exchange during 2020–2024, as measured by Return on Assets, and to examine the moderating role of firm size in these relationships. A quantitative approach with a causal-associative design was employed, involving 12 banking companies selected through purposive sampling from 46 IDX-listed banks. Data were obtained from Bloomberg Terminal for ESG pillar scores and audited annual financial reports and were analyzed using Moderated Regression Analysis with IBM SPSS Statistics. The findings show that Environmental Disclosure and Governance Disclosure have positive and significant effects on Return on Assets, whereas Social Disclosure has a significant negative effect. Firm size positively affects Return on Assets and moderates all three ESG–financial performance relationships by weakening the positive effects of Environmental and Governance Disclosure while mitigating the negative effect of Social Disclosure. These findings indicate that ESG dimensions do not uniformly enhance banking profitability and that firm size shapes the financial implications of ESG disclosure. The study contributes to the development of legitimacy theory and stakeholder theory in sustainable banking and extends understanding of size-contingent ESG effects in emerging markets. The findings imply that bank management, regulators, and the OJK should adopt size-differentiated ESG disclosure strategies to strengthen sustainable financial performance and support more context-sensitive ESG governance in the Indonesian banking sector.